Early response evaluation by single cell signaling profiling in acute myeloid leukemia - Benedicte Sjo Tislevoll; Monica Hellesøy; Oda Helen Eck Fagerholt; Stein-Erik Gullaksen; Aashish Srivastava; Even Birkeland; Dimitrios Kleftogiannis; Pilar Ayuda-Durán; Laure Piechaczyk; Dagim Shiferaw Tadele; Jørn Skavland; Panagotis Baliakas; et al. (Nature Communications, 2023)
The molecular mechanisms underlying response to chemotherapy in Acute myeloid leukemia (AML) remain to be explored. Here, the authors perform 36-dimensional mass cytometry in 32 AML patients during intensive chemotherapy and suggest functional signalling analysis for prognosis prediction early after treatment in AML.